Solid waste disposal site selection using GIS and the Analytic Hierarchy Process model: a case study conducted in Gimba Town, Northeastern Ethiopia - Sisay, Tesfaldet; Teku, Degfie; Abebaw, Endalkachew (Frontiers in Sustainability, 2025)
IntroductionSolid waste mismanagement, particularly the use of river courses, roadsides, and open spaces for indiscriminate waste disposal, poses significant environmental, socio-economic, and public health challenges in Gimba Town, Northeastern Ethiopia. Addressing this issue requires scientifically sound approaches to identify suitable landfill sites that minimize environmental impacts and support sustainable urban development.MethodsThis study employed an integrated Geographic Information System (GIS) and Analytic Hierarchy Process (AHP) model to identify optimal landfill sites for Gimba Town. Nine thematic criteria built-up areas, slope, proximity to rivers, groundwater withdrawal points, land use/land cover, fault lines, roads, geology, and soil texture were analyzed. The relative weights of each criterion were determined through pairwise comparison using the AHP model to produce a weighted overlay analysis in GIS.ResultsThe AHP results indicated that built-up areas (30.33%), slope (21.95%), and proximity to rivers (15.01%) were the most influential factors in determining landfill suitability. The spatial analysis classified the land into four suitability categories: very highly suitable (2.65 km2), highly suitable (56.91 km2), moderately suitable (78.38 km2), and unsuitable (26.46 km2). The findings revealed that only a limited area of Gimba Town is appropriate for landfill development.DiscussionThe study highlights the importance of data-driven, multi-criteria decision-making tools in solid waste management planning. Integrating GIS and AHP proved effective in generating a replicable framework for landfill site selection, enhancing environmental sustainability and minimizing health risks. These results provide critical insights for policymakers, urban planners, and local authorities in designing sustainable solid waste management strategies tailored to the specific context of Gimba Town.